2017
DOI: 10.1103/physrevlett.118.099903
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Spatially Assisted Schwinger Mechanism and Magnetic Catalysis [Phys. Rev. Lett. 117 , 081603 (2016)]

Abstract: [This is an erratum applied version to Phys. Rev. Lett. 117, 081603 (2016). The conclusion is not changed, but we should have considered not decreasing but increasing spatial modulations in the magnetic profile.] Using the worldline formalism we compute an effective action for fermions under a temporally modulated electric field and a spatially modulated magnetic field. It is known that the former leads to an enhanced Schwinger Mechanism, while we find that the latter can also result in enhanced particle produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Among all the circumstances for anomaly, the one with parallel electromagnetic (PEM) field is specific because the background is already parity-violating even without involving any matter. In our previous studies [37,38], neutral pseudo-scalar mesons were found to condensate under the PEM field; and P. Copinger and K. Fukushima discovered that the Schwinger pair production (SPP) rate is enhanced by a semilocalized static magnetic field [39]. Furthermore, there is one very im-portant discovery for the chiral anomaly dynamics [40]: In order to understand the contradiction between massless case and small mass limit for chiral anomaly ∂ µ J µ 5 , one has to adopt the in-in (or real-time) rather than the in-out (or imaginary-time) propagator for the fermions.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the circumstances for anomaly, the one with parallel electromagnetic (PEM) field is specific because the background is already parity-violating even without involving any matter. In our previous studies [37,38], neutral pseudo-scalar mesons were found to condensate under the PEM field; and P. Copinger and K. Fukushima discovered that the Schwinger pair production (SPP) rate is enhanced by a semilocalized static magnetic field [39]. Furthermore, there is one very im-portant discovery for the chiral anomaly dynamics [40]: In order to understand the contradiction between massless case and small mass limit for chiral anomaly ∂ µ J µ 5 , one has to adopt the in-in (or real-time) rather than the in-out (or imaginary-time) propagator for the fermions.…”
Section: Introductionmentioning
confidence: 99%